Penyusunan Rencana Pembangunan Desa Berdasarkan Data Sarana Dan Prasarana Dalam Sistem Informasi Desa Pada Desa Teratak, Kec. Rumbio Jaya, Kab. Kampar, Provinsi Riau - Daffeta Fitrilinda; Fitra Herlinda; Mahmu Datu Rahma; Dwi Joyandanila; Dzaskhia Delvani Putri; Elvira Zahera; Haziq Hidayatullah; Firdah Mahirah; Windi Oktavia; Feris Adek Subagia; Raja Ardika (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Village development plan preparation activies are carried out using a database that is already in the SID. Some of the data that will be used is village facilities and indrastructure data. The aim of this years PKM activity is to Provide Guidance to village government officials in preparing village development plans based on village facilities and infrastructure data in the SID. The method that will be used by the PKM team will be carried out in two stages of activity. This stage of activity begins with the preparation stage and then continues with the implementation stage. Preparation stage activities include: Coordination with village Apparatus, division of colloborative tasks with village apparatus and PKM team, collection and grouping of digital and non digital data, compilation of facilities and infrasrtucture data in SID. Meanwhile the activity implementaion stages include.: Evaluation of the previous RPJMDes, formation of the drafting tea, meeting of the drafting team in the context of aglining develpment policy direction, preparation of planning and design of the RPJMDes, determination of the RPJMDes. The impact of this activity is (1) The village has a village development planning document refeering to the complete, accurate and up to date condition of village facilities and infrastructure via SID. (2) The village has village government officials who are skilled at managing the village information system and utilizing it to improve community contributes to the preparation of village development planning by providding information directly through SID.